Formative Assessment: Energizing Learning, Empowers Teaching - Saoud, Ammar (جامعة الوادي - university of Eloued, 2020)
BSTRACT The impact of formative assessment on students’ achievement has recently received wider recognition and growing interest among researchers and educators. The present article tackles the specificities of formative assessment in English language education.It discusses some key issues surrounding classroom assessment ranging from conceptual definitions to practical implications. It also reviews the different roles of teachers and students within the formative assessment process. In addition, some defining characteristics and key principles are explored with a particular focus on the ongoing cycle of formative assessment (before-during-after instruction).Subsequently, the paper highlights the five key strategies of quality and effective assessment, and finally, it critically examines the significance of formative assessment by centering much attention on both students’ achievement and motivation as well as teachers’ efficacy.
مقال
Keywords: Classroom Assessment; Formative Assessment; Students' Achievement; Teacher's efficacy; teaching/learning process